Expressive Act by Elite Politicians in Responding Issue of “Coup d’etat” in Democratic Party” - Yohanes Moruk; Upi Laila Hanum; Lewi Kabanga' (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Democratic party is one of the greater parties that exists in Indonesia. Its existence gives significance colors in national politics. The declaration of coup’ d etat effort in front of the pers invites the politicians giving their responds. This research tries to investigate expressive act by the elite politicians. The method used in this research was qualitative method. To collect the data, documentation technique was used. It meant that the data were downloaded from internet. There were six videos taken from internet with 12 politicians. Those videos discussed the issue of coup d’etat in democratic party. The collecting data were transcribed without blurring the meaning. In displaying the data, the researchers investigated expressive acts used by every politician and then put them into the table of expressive acts. The results of this research revealed that there were two groups of politicians with different expressive acts. The group of pro and contra toward the issue of coup d’etat. In pro group used expressive act of approving, convincing, confessing, criticizing, and fearing. While the contra used disapproving, resentment, shocking and lamenting. Whole the expressive acts, both in pro and contra, were categorized into psychological and attitude effects. The psychological effect included the emotional range such as fearing, shocking, lamenting, and resentment. While, the attitude effect included the range of cognition, affection, and connation such as approving, disapproving, convincing, confessing, and criticizing. The implying meaning showed both the existence of coupd’etat and conspiracy thinking of elite politicians.